Evaluación del Impacto del bono Joaquín Gallegos Lara en la Ciudad de Loja, Ecuador - Cuenca Ávila, Dalila Ester (2025)
This research analyzes the impact of the Joaquín Gallegos Lara bond on the well-being of people with severe disabilities and catastrophic illnesses in the city of Loja, Ecuador. This bond implemented by the Ecuadorian Government through monetary transfer programs for people with severe disabilities and catastrophic illnesses, seeks to alleviate the economic issue of caregiver families and improve the quality of life of people facing limiting health conditions. The study is based on data provided by the Ministry of Economic and Social Inclusion (MIES), analyzing sociodemographic variables through a probit model and marginal effects to determine the probability of access to the bond through independent variables such as type of disability, area, sex and type of beneficiary, percentage of disability, type of beneficiary. The results show that there is a greater probability that people have access to this monetary transfer if people belong to the rural area; likewise, there is a greater possibility that females will access this system and be beneficiaries, as belonging to the area increases the probability of access to the Joaquín Gallegos Lara bond. In addition, a high proportion of beneficiaries with low levels of education and limited access to health services are observed. However, the study underlines the need for a comprehensive approach to social protection policies, combining economic support with additional strategies to maximize the impact and quality of life of the beneficiaries.